Wasted Food - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
About 300 million people could be fed just by saving annual post-harvest losses of cereal grains and legumes in the Third World, according to a recent report from the United Nations Environment Programme (UNEP). Inadequate drying, improper...